A Building Information Modeling Based Automated Rule-Checking Application for Zoning Regulation Compliance: The Case of Turkiye - Yılmaz, Cengiz; Dikbaş, Hüseyin Atilla (Fırat Üniversitesi, 2025)
The aim of this study is to develop an automated rule-checking application that enables the rapid, transparent, and efficient verification of building design data, created through Building Information Modeling (BIM), in compliance with zoning regulations during the design and approval phases of construction projects in Turkiye. In this context, rules expressed in regulatory texts were transformed into a format adaptable to software using propositional logic, and decision structures were created. Distinctive parameters based on the rules to be checked were assigned to the BIM environment. Model data were exported in the shareable Industry Foundation Classes (IFC) format, and a Python-based software was developed to test the automated rule-checking method on four different sample projects, generating result reports. The findings show that regulatory provisions can be converted into logical structures and compared with Industry Foundation Classes data, making it possible to digitally assess a project’s compliance with regulations. This approach could contribute to enabling public authorities to implement a more effective and transparent control mechanism in the design and approval processes. The originality of the study lies in the successful application of classical propositional logic—despite its lack of complex logical operators—to complex regulatory rules. Moreover, the set of validated propositions not only defines the outcome of the rule check but also provides comprehensive contextual information related to the rule, allowing for a more in-depth evaluation of the results.

Türkiye’de inşaat projelerinin tasarım ve onay aşamalarında, yapı bilgi modellemesi (YBM) ile oluşturulan proje verilerinin imar mevzuatına uygunluğunu hızlı, şeffaf ve verimli biçimde denetlemeye olanak tanıyan bir otomatik kural kontrolü uygulaması geliştirilmesi bu çalışmanın temel amacını oluşturmaktadır. Bu kapsamda, mevzuat metinlerinde yer alan kurallar önermeler mantığı esas alınarak yazılım diline uyarlanabilir bir yapıya dönüştürülmüş, karar yapıları oluşturulmuş ve YBM ortamına aktarılacak ayırt edici parametreler tanımlanmıştır. Model verileri, paylaşıma açık olan Endüstri Temel Sınıfları (Industry Foundation Classes, IFC) formatında dışa aktarılmış ve Python diliyle geliştirilen yazılım aracılığıyla dört farklı örnek proje üzerinde test edilerek otomatik denetim raporları elde edilmiştir. Elde edilen bulgular, mevzuat kurallarının mantıksal yapılara dönüştürülerek Endüstri Temel Sınıfları veri yapılarıyla karşılaştırılabileceğini ve böylece yapı projelerinin mevzuata uygunluğunun dijital ortamda denetlenebileceğini göstermektedir. Bu yaklaşım, kamu otoritelerinin tasarım ve onay süreçlerinde daha etkin ve şeffaf bir kontrol mekanizması geliştirmelerine katkı sağlayabilir. Çalışmanın özgün yönü, klasik mantık sisteminde yer alan ve karmaşık mantıksal operatörler içermeyen önermeler mantığının, yönetmeliklerdeki girift kurallara uygulanabilmiş olmasıdır. Ayrıca elde edilen doğru önermeler kümesi, yalnızca kural ihlalini göstermekle kalmayıp, ilgili kuralın kapsamlı bir analizini mümkün kılan tamamlayıcı bilgilerle birlikte sunulmaktadır.
İmar Mevzuatına Uygunluk Denetimi için Yapı Bilgi Modellemesi Tabanlı Otomatik Kural Kontrolü Uygulaması: Türkiye Örneği
Keywords: Building Technology; Yapı Teknolojisi; Building (Other); Yapı (Diğer)